HIV mortality across the 30 largest U.S. cities: assessing overall trends and racial inequities. Issue 7 (3rd July 2022) - Benjamins, Maureen R.; Saiyed, Nazia; Bunting, Samuel; Lorenz, Peter; Hunt, Bijou; Glick, Nancy; Silva, Abigail
ABSTRACT: Background: Despite decreases in overall HIV mortality in the U.S., large racial inequities persist. Most previous analyses of HIV mortality and mortality inequities have utilized national- or state-level data. Methods: Using vital statistics mortality data and American Community Survey population estimates, we calculated HIV mortality rates and Black:White HIV mortality rate ratios (RR) for the 30 most populous U.S. cities at two time points, 2010–2014 (T1) and 2015–2019 (T2). Results: Almost all cities (28) had HIV mortality rates higher than the national rate at both time points. At T2, HIV mortality rates ranged from 0.8 per 100, 000 (San Jose, CA) to 15.2 per 100, 000 (Baltimore, MD). Across cities, Black people were approximately 2–8 times more likely to die from HIV compared to White people at both time points. Over the decade, these racial disparities decreased at the national level (T1: RR = 11.0, T2: RR = 9.8), and in one city (Charlotte, NC). Discussion: We identified large geographic and racial inequities in HIV mortality in U.S. urban areas. These city-specific data may motivate change in cities and can help guide city leaders and other health advocates as they implement, test, and support policies and programming to decrease HIV mortality.